Customer purchase intention in Genting Highland Premium Outlet (GHPO) / Mohd Sharul Shafik Asmuni - Asmuni, Mohd Sharul Shafik (Faculty of Business and Management, 2018)
This Research study is aimed to identify the factors of customer purchase intention in Genting Highland Premium Outlet, Pahang. The elements that will be examined were environment, tenant variety and promotion. Convenient sampling technique was used and adapted. Questionnaires were been adapted from various research journals that related to the topic and been distributed to 150 respondents around Kuala Lumpur area. Total 150 questionnaires were collected and were found usable. Data then been analyzed by using SPSS. Hence data been analyzed using several statistical analysis including demographic profile, reliability analysis, correlation test and multiple regression test. Furthermore, the result shows and confirmed that all of the variables are positively related towards customer purchase intention in Genting Highland Premium Outlet. As conclusion, the findings of this research study can be beneficial especially to the management of Genting and product brand.